Security Analysis And Improvements Of Acess Control In The Internet Of Things - et. al., S. Vijaya Lakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things is an omnipresent concept with physical objects connecting with the Internet and programmed with specific identifications to guarantee that they can recognise and continuously gather and share data over a network. The Internet of Things As a consequence, the security of data sharing and interconnected sensor nodes grows very rapidly, the safety of network, data and sensor devices is a major concern of the IoT network. This paper analyses the authentication system and the Internet of Things access management. protocol is costly for exchanging packets and according to our study the security assessment is not sufficient enough for such a protocol. We therefore suggest changes to the protocol to fill the holes observed. The protocol enhancements allow for many user services, including anonymity, mutual authentication and a secure session key configuration. Finally, the efficiency and safety assessment reveals that the improved protocol provides several advantages over common attacks, improving stability at low connection costs. The Philosophy of the Internet Interconnection to the Internet helped objects or devices to achieve certain common goals for each other and for people. IoT should be integrated seamlessly in our society in the near future and citizens will fully depend on this technology for comfort and simplicity. In a single paper, we tried to make improvements and access control techniques accessible.